PEMBAHARUAN LETTER OF COORDINATION AGREEMENT ANTARA AIR TRAFFIC SERVICE REPORTING OFFICE DENGAN OPERATOR PENERBANGAN TERHADAP PENANGANAN PELAYANAN AIR TRAFFIC SERVICE MESSAGE DI PERUM LPPNPI CABANG DENPASAR - Safira Ayu Laksono; Lusiana Dewi Kusumayati; Yeni Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study aims to determine the cause of the need to update the LOCA between the ATS Reporting Office (ARO) and the Flight Operators at Perum LPPNPI Denpasar Branch. With the existence of a new unit called Ngurah Delivery which provides ATC clearance services the fastest 20 minutes before Estimate Off Block Time (EOBT). This is not in accordance with the written LOCA "the flight operator must notify the ARO officer of the changes contained in the proposed FPL no later than 15 (fifteen) minutes before the EOBT".The method used to analyze the data is descriptive qualitative analysis technique, using data collection methods, observation methods, interviews and documentation.. The population of this research is Aeronautical Communication Officer (ACO) personnel at Perum LPPNPI Denpasar Branch, while the authors take several samples from the population, namely ACO personnel at Perum LPPNPI Denpasar Branch. The results of this study prove that the LOCA that exists between the ARO Unit and other airline operators is a problem for the handling and responsibilities of an aircraft which when it requires immediate service in the field as well as hampering the efficiency of providing flight services by Aeronautical Communication Officer personnel. (ACO).